2010
DOI: 10.1007/s10342-010-0408-x
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth and time-varying climate response along altitudinal transects in central China

Abstract: We present six tree-ring chronologies from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
(19 reference statements)
3
7
0
Order By: Relevance
“…High temperatures in autumn may accelerate the evaporation of soil water, causing drought stress and subsequently limiting tree growth, although precipitation would also increase (Fang et al. ). Additionally, high temperatures during the growing season could exacerbate respiration and limit the uptake of nutrients that are needed for growth (Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures in autumn may accelerate the evaporation of soil water, causing drought stress and subsequently limiting tree growth, although precipitation would also increase (Fang et al. ). Additionally, high temperatures during the growing season could exacerbate respiration and limit the uptake of nutrients that are needed for growth (Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our low correlation between growth and precipitation, drought stress likely has an impact on growth of trees in the region. Several studies from central and SE China have shown high correlations between Palmer Drought Severity Index (PDSI) and growth [5], [8], [43], [46]. Also, growth of P. tabuliformis has been shown to be sensitive to drought in northern China [6], [44], [45].…”
Section: Discussionmentioning
confidence: 99%
“…Response is not likely to be consistent across all of JNNR for a given species. Several studies have demonstrated variable growth response to climate, depending on topographic position [3], [5], [43], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Bigler et al, 2004;Gray et al, 2004;Muzika et al, 2004;Büntgen et al, 2006;Carrer and Urbinati, 2006;Koprowski and Zielski, 2006;Esper et al, 2007;Büntgen et al, 2007;Čejková and Kolář, 2009;Feliksik and Wilczyński, 2009;Bijak, 2010;Fang et al, 2010;Bošeľa et al, 2011;Bošeľa et al, 2014;Dittmar et al, 2012;Hökkä et al, 2012), and studies using more than two cores or discs are less frequent (e.g. Brienen and Zuidema, 2005;Ďurský et al, 2006;Van Der MaatenTheunissen et al, 2013) because they are costly and destructive.…”
Section: Introductionmentioning
confidence: 99%
“…Cook and Kairiukstis, 1990;Schweingruber, 1996;Pretzsch, 2009). For such analysis, core extraction via increment borer has become standard practice (Hasenauer et al, 1999;Bigler et al, 2004;Carrer and Urbinati, 2006;Metsaranta and Lieffers, 2009;Fang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%